Design and validation of a self-administered questionnaire as an aid to detection of occupational exposure to lung carcinogens. (February 2017) - Pélissier, C.; Dutertre, V.; Fournel, P.; Gendre, I.; Michel Vergnon, J.; Kalecinski, J.; Tinquaut, F.; Fontana, L.; Chauvin, F.
Abstract: Objective: Ten to thirty percent of lung cancer is thought to be of occupational origin. Lung cancer is under-declared as an occupational disease in Europe, and most declarations of occupational disease concern asbestos. The purpose of this study was to design and validate a short, sensitive self-administered questionnaire, as an aid for physicians in detecting occupational exposure to asbestos and other lung carcinogens in order to remedy occupational lung cancer under-declaration. Study design: Cross-sectional study. Methods: A short (30-question) self-administered questionnaire was drawn up by oncologist-pneumologists and occupational physicians, covering situations of exposure to proven and probable lung carcinogens. Understanding and acceptability were assessed on 15 lung cancer patients. Validity and reliability were assessed on 70 lung cancer patients by comparison against a semi-directive questionnaire considered as gold standard. Sensitivity and specificity were assessed by comparing responses to items on the two questionnaires. Reliability was assessed by analysing the kappa concordance coefficient for items on the two questionnaires. Results: Sensitivity was 0.85 and specificity 0.875. Concordance between responses on the two questionnaires was 85.7%, with a kappa coefficient of 0.695 [0.52–0.87]. Mean self-administration time was 3.1 min (versus 8.12 min to administer the gold-standard questionnaire). In 16 patients, the self-administered questionnaire detected lung carcinogen exposure meeting the criteria for occupational disease. Conclusion: The present short, easy-to-use self-administered questionnaire should facilitate detection of occupational exposure to lung carcinogens. It could be used in occupational lung cancer screening and increase the presently low rate of application for recognition of lung cancer as an occupational disease. Highlights: Lung cancer is presently under-declared as an occupational disease. Lack of a rapid tool to identify occupational exposure to lung carcinogens. Design self-administered questionnaire to facilitate detection of lung carcinogens. Assessment of reliability and validity of the self-administered questionnaire. Tool to increase lung cancer recognition as an occupational disease.